Деякі міркування щодо віднесення наукової спеціальності “Документознавство, архівознавство” до галузі науки “Соціальні комунікації” - Кулешов, С. (Архіви України, 2008)
The article covers the author’s attitude towards recent changes further to Order of the Higher Attestation Commission dated December 14, 2007 #867, respecting defense of thesis, awarding scientific degrees and academic titles, implementation of a new “Social Communications” branch of science.